Privatization Policy in an International Oligopoly - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2003)
This paper studies privatization policy in an international oligopoly. The argument that equal treatment of foreign investors will be detrimental to domestic welfare by shifting profits from domestic to foreign firms is shown to be less relevant in privatization auctions than in greenfield FDI models, since these profit shifts are partly paid for by the foreign firms in the bidding competition. Effects of local equity requirements, trade and investment policies are also studied. It is, for instance, shown that small local equity requirements are likely to be beneficial but large ones are counterproductive, by preventing welfare-enhancing foreign acquisitions.
Keywords: F23; L13; L33; 330; Privatization; Acquisitions; National Treatment; Investment Policy; Trade Policy; Privatisierung; Oligopol; International; Direktinvestition; Theorie